Activity evaluation and reaction mechanisms of highly efficient dual-atom transition metal catalysts in Li-CO2 batteries - Jinhui Zhang; Yao Liu; Tengwen Yan; Guanghui Jin; Yajing Shen; Jing Xu; Dashuai Wang (Next Materials)
Lithium-carbon dioxide (Li-CO2) batteries have received increased attention due to their high energy density and fixing CO2 as a major greenhouse gas. At the same time, there are challenges including low activity of cathode and high overpotential in Li-CO2 batteries. Herein, 45 dual-atom catalysts (DACs) composed of 9 transition metal (TM) atoms doped in nitrogen-doped graphene (M1M2-N-G, M1, M2 = Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), as cathode catalysts of Li-CO2 batteries, have been studied by using first-principles calculations. According to the thermodynamic stability of the DACs and the ability of CO2 activation, 25 catalysts candidates were screened out. Then, the reaction activity and selectivity of DACs were evaluated by thermodynamical reaction energy and overpotential. Finally, TiMn-N-G displayed the smallest total electrode overpotential 1.83 V during the pathway of Li2CO3 and CrNi-N-G exhibited the smallest total electrode overpotential 0.08 V during the in Li2C2O4 pathway, respectively, which proved that they possessed better catalytic activity tendency in Li-CO2 batteries. This work provides not only a rational design to identify promising graphene-based catalysts, but also a general screen rule for atomic catalysts in Li-CO2 batteries.